2013
DOI: 10.1155/2013/810590
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma Associated with Xp11.2 Translocation/TFE3 Gene Fusion: A Rare Case Report with Review of the Literature

Abstract: Introduction. The recently recognized renal cell carcinomas associated with Xp11.2 translocations are rare tumors predominantly reported in children. Chromosome Xp11.2 translocation results in gene fusion related to transcription factor E3 (TFE3) that plays an important role in proliferation and survival. Case Report. Herein, we present two cases of a TFE3 translocation-associated RCC in young female adults, one detected incidentally and the other one presenting with gross hematuria. Tumor is characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 4 publications
2
25
0
2
Order By: Relevance
“…Pathologists should take into account the possibility that Xp11. [1,18,20,22,23,24,25,26,27,28,29,30]. However, in the present study most patients were males, as reported in previous studies [21,31,32,33].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Pathologists should take into account the possibility that Xp11. [1,18,20,22,23,24,25,26,27,28,29,30]. However, in the present study most patients were males, as reported in previous studies [21,31,32,33].…”
Section: Discussionsupporting
confidence: 68%
“…In 30% of tumours, patients present with metastasis. The prognosis of patients with RCC varies according to the stage and histological grade [1]. In Saudi Arabia, renal tumours constitute 3.6% of all tumours in males and 2.2% in females.…”
Section: Introductionmentioning
confidence: 99%
“…The most common treatment of Xp11.2 RCC is similar to that for conventional RCC. For localized Xp11.2 RCC with positive regional lymph nodes, surgery is the optimal treatment (18). If the tumor is sized <7 cm, nephron-sparing surgery is considered as a treatment option (19).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the optimal treatment for localized Xp11.2 RCC patients, including those with positive regional lymph nodes 7 . However, previous studies indicate that Xp11.2 RCC presents at an advanced stage with a rapid clinical course 8,9 .…”
mentioning
confidence: 99%